Accuracy and Effectiveness of Mammography versus Mammography and Tomosynthesis for Population-Based Breast Cancer Screening: A Systematic Review and Meta-Analysis - Giampietro, Rodrigo Rosa [UNESP]; Gama Cabral, Marcos Vinicius [UNESP]; Molina Lima, Silvana Andrea [UNESP]; Theresa Weber, Silke Anna [UNESP]; Nunes-Nogueira, Vania dos Santos [UNESP] (Nature Publishing Group, 2020)
We proposed to compare the accuracy and effectiveness of digital breast tomosynthesis (DBT), plus digital or synthetic mammography, with digital mammography alone in women attending population-based breast cancer screenings. We performed a systematic review and included controlled studies comparing DBT with digital mammography for breast cancer screening. Search strategies were applied to the MEDLINE, Embase, LILACS, and CENTRAL databases. With moderate quality of evidence, in 1,000 screens, DBT plus digital mammography increased the overall and invasive breast cancer rates by 3 and 2 (RR 1.36, 95% CI 1.18 to 1.58 and RR 1.51, 95% CI 1.27 to 1.79, respectively). DBT plus synthetic mammography increased both overall and invasive breast cancer rates by 2 (RR 1.38, 95% CI 1.24 to 1.54 and RR 1.37, 95% CI 1.22 to 1.55, respectively). DBT did not improve recall, false positive and false negative rates. However due to heterogeneity the quality of evidence was low. For women attending population-based breast cancer screenings, DBT increases rates of overall and invasive breast cancer. There is no evidence with high or moderate quality showing that DBT compared with digital mammography decreases recall rates, as well as false positive and false negative rates.